Time Course of the Soleus M Response and H Reflex after Lidocaine Tibial Nerve Block in the Rat - Kévin Buffenoir; Philippe Decq; Chantal Pérot (The Scientific World Journal)
Aims. In spastic subjects, lidocaine is often used to induce a block predictive of the result provided by subsequent surgery. Lidocaine has been demonstrated to inhibit the Hoffmann (H) reflex to a greater extent than the direct motor (M) response induced by electrical stimulation, but the timecourse of these responses has not been investigated. Methods. An animal (rat) model of the effects of lidocaine on M and H responses was therefore developed to assess this time course. M and H responses were recorded in 18 adult rats before and after application of lidocaine to the sciatic nerve. Results. Two to five minutes after lidocaine injection, M responses were markedly reduced (mean reduction of 44%) and H reflexes were completely abolished. Changes were observed more rapidly for the H reflex. The effects of lidocaine then persisted for 100 minutes. The effect of lidocaine was therefore more prolonged on the H reflex than on the M response. Conclusion. This study confirms that lidocaine blocks not only alpha motoneurons but also Ia afferent fibres responsible for the H reflex. The authors describe, for the first time, the detailed time course of the effect of lidocaine on direct or reflex activation of motoneurons in the rat.